2011
DOI: 10.2134/agronj2010.0467
|View full text |Cite
|
Sign up to set email alerts
|

‘TifEagle’ Bermudagrass Response to Plant Growth Regulators and Mowing Height

Abstract: Ultradwarf bermudagrass [Cynodon dactylon (L.) Pers. × C. transvaalensis Burtt‐Davy] cultivars require considerable field research to determine best management practices for successful long‐term culture. A field study was conducted in 2004 and 2005 on an experimental ‘TifEagle’ bermudagrass putting green in Clemson, SC, to examine effects of plant growth regulators (PGRs) applied bimonthly and three mowing heights on turf performance. The PGRs included ethephon [(2‐chloroethyl)phosphonic acid] at 1.91 kg a.i. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 31 publications
1
31
3
Order By: Relevance
“…The use of type II growth regulators generally provides visual symptoms of phytotoxicity when applied in grams (Heckman, et al 2001;McCullough et al 2005;McCarty et al 2011), a similar effect caused by the use of ALS inhibiting herbicides (McDonald et al 2006). Some research has shown that the deleterious effects of injury caused by trinexapac-ethyl and bispyribac-sodium may be rapidly reversed with the use of an additional source of iron or nitrogen, which play an important role in the formation of chlorophyll, which gives back the grass leaves their green coloring (Johnson, 1997, Zhang et al 2002Ervin et al 2004;McDonald et al 2006).…”
Section: O N T R O L C O N T R O Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of type II growth regulators generally provides visual symptoms of phytotoxicity when applied in grams (Heckman, et al 2001;McCullough et al 2005;McCarty et al 2011), a similar effect caused by the use of ALS inhibiting herbicides (McDonald et al 2006). Some research has shown that the deleterious effects of injury caused by trinexapac-ethyl and bispyribac-sodium may be rapidly reversed with the use of an additional source of iron or nitrogen, which play an important role in the formation of chlorophyll, which gives back the grass leaves their green coloring (Johnson, 1997, Zhang et al 2002Ervin et al 2004;McDonald et al 2006).…”
Section: O N T R O L C O N T R O Lmentioning
confidence: 99%
“…The occurrence of visual injury, thereby changing the visual quality of the turf, is often reported. Leaf injury varies according to environmental conditions: in temperate regions, dark green spots are observed (Ervin & Koski, 2001;Heckman et al, 2005, McCullough et al, 2006, while discoloration Effect of plant regulators on growth and flowering of 'Meer' ... characterized by yellowing leaves is seen in tropical regions (Heckman et al, 2001, McCullough et al, 2005, McCarty et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The leaf injury types vary with environmental conditions if under temperate climatic conditions -dark green spots occur (ERVIN; KOSKI, 2001;HECKMAN et al, 2005;McCULLOUGH et al, 2006); if under tropical conditions, a yellowish discoloring is likely to occur GAUSSOIN, 2001;McCULLOUGH et al, 2005;McCARTY et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…None of the visual evaluations showed any symptoms of injury in the plant shoots and zero score of phytotoxicity was assigned to all treatments tested. It is noteworthy that in some studies with type II plant growth inhibitors, as currently tested, toxicity symptoms usually occur when applied to grass (Heckman et al, 2001;McCullough et al, 2005;McCarty et al, 2011), which was not observed in this study.…”
Section: Broadleaf Carpet Grass (Axonopus Compressus)mentioning
confidence: 57%